Company Internal Communication Strategy Great Giant Foods When Facing The Covid-19 Pandemic Crisis - Erya, Wian Rahmat; Wardhani, Andy Corry; Aryanti, Nina Yudha (UNIVERSITAS PAKUAN, 2019)
Great Giant Foods (GGF) is one of the company's brand entities in Central Lampung, Lampung Province, which manages food and beverages. Having more than 11,000 employees is the biggest challenge for companies to continue operating and maintaining business stability amidst a pandemic, especially in this case, the policy carried out by the company's management. So this research intends to analyze how GGF manages crises COVID-19 internal communication process. This study uses a qualitative research approach Through interviews with the Internal Company of GGF Lampung, the Emergency Response Team (ERT). Based on the research results in the field, the internal communication process at GGF was carried out with various strategic communication processes through one of the ERT task forces that were newly formed to handle times of crisis. The conclusion of the GGF communication process conveys the key messages well, utilizes the internal media used, and handles realities in the field to reduce communication disruptions. The ERT team made a management strategy approach so the company could face difficult times.